Entrepreneurship as a form of socio-economic adaptation of combatants: ways and sources of financing - І.V. Zhyhlei; Y.B. Kotsiubynska; О.B. Syvak (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
One of the major problems of modern Ukrainian society, escalating from year to year, is the increasing number of people who participated in the military conflict in eastern Ukraine (combatants). Some of them remained in the ranks of the Armed Forces of Ukraine, thereby providing themselves and their families with the means of subsistence; the rest are military personnel who were forced to leave military service due to problems with health; as well as a number of combatants who were temporarily drafted into the ranks of the Ukrainian army to defend Ukraine and subsequently returned to civilian life. Regardless of the category, each group needs psychological adaptation and assistance. However, military personnel who have been forced to leave military service also need socio-economic adaptation due to the fact that most of them have only a military education, experience and, in the civil sphere, feel incapacitated. In view of the above, the purpose of the article is to find effective ways of socio-economic adaptation of military personnel who have been involved in long-term combat conflicts and sources for financing the proper measures, both from the state and from the business side. In particular, one of these ways is to facilitate the initiation of own business by the ATO/JFO participants. From the budget side, these measures can be used to receive funds that come in the form of a military levy, which is currently unspecified and can therefore not be monitored for its use. In addition, it is advisable to provide tax holidays, to simplify taxes and to provide benefits to start-ups. Business can support with providing information and consultations, but it can be effective if it is coordinated at both national and regional levels as well as involving public-private partnerships into such support.